2016
DOI: 10.2983/035.035.0114
|View full text |Cite
|
Sign up to set email alerts
|

Oyster Planting Protocols to Deter Losses to Cownose Ray Predation

Abstract: The utility of shell overlays to oyster (Crassostrea virginica) plantings as a cownose ray (Rhinoptera bonasus) predator deterrence mechanism was examined. Typical industry practice of oyster seed planting was followed in an experimental design employing treatment areas of 0.5-1.0 acre (0.2-0.4 hectare). Areas were prepared in the Lower Machodoc Creek, Virginia, by the initial application of shell to insure a stable substrate under planted seed oysters. Seed oysters were planted using standard industry methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Some investigations have shown that mollusk shell material can increase abundance and diversity in benthic systems [36,[70][71][72][73][74][75][76][77][78]. Other studies found mixed, weak, or no effects [40,[79][80][81][82][83]. But the effects on flow-related ecosystem processes have not been well-studied.…”
Section: Cover Typesmentioning
confidence: 99%
“…Some investigations have shown that mollusk shell material can increase abundance and diversity in benthic systems [36,[70][71][72][73][74][75][76][77][78]. Other studies found mixed, weak, or no effects [40,[79][80][81][82][83]. But the effects on flow-related ecosystem processes have not been well-studied.…”
Section: Cover Typesmentioning
confidence: 99%